Cause and Effect Analysis of Functional Position Preferences of Social Extension Workers After Serving at the Social Service, Community Empowerment and Villages of Jepara Regency - Achmad Nur Fuad; Mamik Indaryani; Ag Sunarno Handoyo (Publikasi Indonesia, 2025)
This study aims to examine the preferences of Social Counselors from the perspectives of potential, motivation, competence, and job satisfaction after they have assumed the Functional Position of Social Extension Officer at the Department of Social Affairs, Community Empowerment, and Village Administration of Jepara Regency. Job preferences often change after an individual assumes a particular position. Preferences may shift over time as the role is carried out, with the misalignment between initial expectations and the realities of the position underlying an individual’s tendency to choose, remain in, or even leave the position as a form of career preference. This research employs a descriptive qualitative approach, with data collected through in-depth interviews, observations, and documentation. Data analysis is conducted using the fishbone diagram to identify the root causes of changes in job preferences. The findings indicate that preferences for the functional position of Social Extension Officer, viewed from the perspectives of potential, motivation, competence, and job satisfaction, reflect an individual’s inclination to choose and remain in the position despite facing significant challenges. The study provides three improvement recommendations: strengthening competencies through independent and collaborative training, developing a more comprehensive evaluation system, and conducting internal advocacy for the provision of budgets and facilities to support extension activities.